PEMBELAJARAN KIMIA ANALITIK DASAR BERBASIS MULTIMEDIA BAGI MAHASISWA CALON GURU KIMIA - Haryani, Sri; Prasetya, Agung Tri; Alauhdin, M (Universitas Negeri Semarang, 2013)
This research aims to design multimedia based teaching materials model of Basic Analytical Chemistry that oriented on the explanation of macroscopic and microscopic level and symbolic, and its implementation to improve the mastery of science concepts and labwork skills of student teacher candidates. The subjects consisted of 27 and 30 students of chemistry education study program who take Basic Analytical Chemistry lecture as control and experimental group respectively. Quasi-experimental design with pretest - posttest control group used in this study, and the differences of pre and post-tests result were assumed as the effects of the treatment. Mastery of concepts and skills of science process measured by description test was analyzed by comparing the value of the normalized gain (N-gain), whereas questionnaires students feedback was analysed with descriptive percentage. Learning basic analytical chemistry using a CD-oriented learning material that oriented on the structure of matter on acid-base and permanganometric titration can improve mastery of concepts and skills of science proces. The highest indicators of science process skills was classifying and the lowest was hypothesize capabilities. The advantages of learning implementations were increasing mastery of the concepts and science process skills and making a fun learning experience among the students.